2019
DOI: 10.1080/02640414.2019.1676526
|View full text |Cite
|
Sign up to set email alerts
|

Psychological characteristics of developing excellence in elite youth football players in English professional academies

Abstract: This mixed-longitudinal prospective study examined the development of psychological characteristics of developing excellence in relation to the career progression of elite youth football players. In a 20-month period, 111 academy football players aged 11-16 completed the Psychological Characteristics of Developing Excellence Questionnaire (PCDEQ) on 1-5 occasions. This combination of single and repeated assessments resulted in a mixedlongitudinal sample of 226 completed PCDEQs. Players were then prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…More recent research supports such findings showing that future professional soccer players outperformed their non-professional counterparts in measures of speed (5/10/20-m sprint times), power (countermovement jump height), and endurance (distance covered in yoyo intermittent recovery test level 1) from age ~13/14 years onward [39]. Similar findings have also been shown when investigating psychological [50], tactical [51] and technical [52] characteristics, as well as multidimensional research designs [53]. For instance, Forsman et al [53], found future elite players outscored non-elite players, at 15 years of age, in tests of dribbling and passing, passing and centering (technical), speed, agility, endurance (physical), motivation (psychological), and "acting in changing situations" (tactical).…”
Section: Prospective/retrospective Research Designssupporting
confidence: 72%
“…More recent research supports such findings showing that future professional soccer players outperformed their non-professional counterparts in measures of speed (5/10/20-m sprint times), power (countermovement jump height), and endurance (distance covered in yoyo intermittent recovery test level 1) from age ~13/14 years onward [39]. Similar findings have also been shown when investigating psychological [50], tactical [51] and technical [52] characteristics, as well as multidimensional research designs [53]. For instance, Forsman et al [53], found future elite players outscored non-elite players, at 15 years of age, in tests of dribbling and passing, passing and centering (technical), speed, agility, endurance (physical), motivation (psychological), and "acting in changing situations" (tactical).…”
Section: Prospective/retrospective Research Designssupporting
confidence: 72%
“…The present study provides a first step in the validation process of a formative assessment tool for the developmental psychological characteristics in athletes between 7 and 13 years old, called the PCDEQ-C. Rather than a talent selection tool, this questionnaire should be used as a formative assessment tool to monitor, develop, and design the psychological characteristics needed during the entire TDE pathway of a young, potential athlete. The questionnaire is being increasingly reported as a practical and comprehensive tool to measure PCDEs by both athletes and coaches [ 47 ] and should be used as part of the triangulation process. The use of other measures, such as behavioural observations, coaches’ opinions, dialogue with family or guardians, and follow-up of the PCDEQ-C results by coaches and/or sport psychologist are advised.…”
Section: Discussionmentioning
confidence: 99%
“…Millions of children around the world are involved in soccer [25,26]. Although most children play soccer recreationally, the number of them who are federated from a very young age by joining a professional club has increased notably [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Millions of children around the world are involved in soccer [25,26]. Although most children play soccer recreationally, the number of them who are federated from a very young age by joining a professional club has increased notably [25,26]. It is well known that practicing soccer has beneficial effects on numerous health parameters of children and adolescents [27][28][29].…”
Section: Discussionmentioning
confidence: 99%